Mood regulation in euthymic patients with a history of antidepressant-induced mania - Halabi, Ramzi; Yusuff, Khairatun; Park, Clara; DeShaw, Alexandra; Gonzalez-Torres, Christina; Husain, Muhammad I; O'Donovan, Claire; Alda, Martin; Mulsant, Benoit H; Ortiz, Abigail (Bipolar disorders, 2024)
INTRODUCTION: The use of antidepressants in bipolar disorder (BD) remains contentious, in part due to the risk of antidepressant-induced mania (AIM). However, there is no information on the architecture of mood regulation in patients who have experienced AIM. We compared the architecture of mood regulation in euthymic patients with and without a history of AIM. METHODS: Eighty-four euthymic participants were included. Participants rated their mood, anxiety and energy levels daily using an electronic (e-) visual analog scale, for a mean (SD) of 280.8(151.4) days. We analyzed their multivariate time series by computing each variable's auto-correlation, inter-variable cross-correlation, and composite multiscale entropy of mood, anxiety, and energy. Then, we compared the data features of participants with a history of AIM and those without AIM, using analysis of covariance, controlling for age, sex, and current treatment. RESULTS: Based on 18,103 daily observations, participants with AIM showed significantly stronger day-to-day auto-correlation and cross-correlation for mood, anxiety, and energy than those without AIM. The highest cross-correlation in participants with AIM was between mood and energy within the same day (median (IQR), 0.58 (0.27)). The strongest negative cross-correlation in participants with AIM was between mood and anxiety series within the same day (median (IQR), -0.52 (0.34)). CONCLUSION: Patients with a history of AIM have a different underlying mood architecture compared to those without AIM. Their mood, anxiety and energy stay the same from day-to-day; and their anxiety is negatively correlated with their mood.
Keywords: Male; afekt; cross‐correlation; time series analysis; euthymia; Anxiety; Adult; dospělí; mužské pohlaví; mánie; auto‐correlation; Affect; úzkost; lidé; ženské pohlaví; bipolar disorder; Humans; antidepresiva; mood regulation; psychiatrické posuzovací škály; Female; Antidepressive Agents; Mania; lidé středního věku; Psychiatric Status Rating Scales; bipolární porucha; antidepressant‐induced mania (AIM); Middle Aged; Bipolar Disorder